OPTIMIZATION AS THE BASIS FOR PLANNING OF CHANGE IN THE REGULATORY POLICY OF THE DEVELOPMENT OF NATIONAL ECONOMY (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The development and implementation of an effective regulatory policy is an important step of the state aimed at increasing the ability to respond to changes and the effectiveness of managing them, and also allowing directing the vector of regulatory influence in the right direction.The goal of the article is to improve the process of optimizing changes in the regulatory policy of national economy development.The stages of the development optimization process indices and regulatory policy of national economy development are constructed and disclosed. The matrix of coefficients determination of domains weights in national economy by means of the comparative advantages method is constructed. The correlation between the aggregate development aggregate index and the aggregate regulatory policy index is calculated and constructed. On the basis of optimal indices the generalized regulatory policy indices for the spheres are determined with their subsequent summation taking into account the weight of the spheres. It is established that the optimal value of aggregate index of the national economy development is 1.221.The research results serve to the changes process optimization in regulatory policy as well as their improvement. Unlike others they provide differentiation of spheres by the need to accelerate development and changes in regulation based on a matrix of comparative advantages, the definition of aggregated indices of development and generalizable indices of regulatory policy between sectors, them and the solution of the optimization problem taking into account the revealed limitations of the marginal expediency of growth (decrease) of generalized regulatory indices policy by branches of the national economy and limited opportunities to increase the values of these indicators.
Keywords: change optimization, regulatory policy, national economy, planning, development.